NILAI – NILAI PENDIDIKAN KARAKTER DALAM DORAMA ONE LITRE OF TEARS PADA TOKOH IKEUCHI AYA - Medy Muammar; Nana Rahayu; Yenni Aristia Nasution (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: this research aimed at knowing values of education character in dorama one litre of tears. This research used some theories form MEXT (2012), Thomas Lickona (1998), and David McCullough (2010). The used method was qualitative descriptive. The object was a Japanese drama called One Litre of Tears. The result shows us there are values of character education in form of value of wholehearted, value of friendship, value of thank and respect, value of family respect, value of responsibility, value of nature respect and value of live respect. Those values appeared by involving moral knowledge, moral awareness, and moral action as part of character which affect each others.Keywords: Values, Education Character, Moral